2016
DOI: 10.2334/josnusd.15-0491
|View full text |Cite
|
Sign up to set email alerts
|

Headache attributed to temporomandibular disorders and masticatory myofascial pain

Abstract: We investigated the temporal association between temporomandibular disorders (TMD)-related symptoms and headache during TMD treatment for patients who fulfilled the diagnostic criteria for headache attributed to TMD (HATMD) specified in the Diagnostic criteria for TMD (DC/TMD) and International classification of headache disorders (ICHD)-3 beta. The study enrolled 34 patients with HATMD induced by masticatory myofascial pain but not by temporomandibular arthralgia. Facial pain intensity, the pressure pain thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
3
29
0
2
Order By: Relevance
“…This further agrees with Hara et al. 24 , who found that headache and myofascial pain are strongly correlated to TMJ health status. 24 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This further agrees with Hara et al. 24 , who found that headache and myofascial pain are strongly correlated to TMJ health status. 24 .…”
Section: Discussionsupporting
confidence: 93%
“…24 , who found that headache and myofascial pain are strongly correlated to TMJ health status. 24 . Clicking was found to be a frequent symptom among KAU-DH patients (42%) of patients with TMD.…”
Section: Discussionmentioning
confidence: 99%
“…TMDH has been listed as 1 of 12 most common types of TMD, with prevalence ranging between 1 and 5.7% . Recent studies suggest that TMDH is amenable to the management of TMD . Patients with TMDH exhibited a significantly increased pressure pain threshold (PPT) in the temporalis muscles, while TMD patients without TMDH had a significantly increased PPT in the masseter muscles .…”
Section: Introductionmentioning
confidence: 99%
“…In the SM group, patients were instructed to follow a home exercise program that included stretching and massaging of their masseter, temporal, sternocleidomastoid, and trapezius muscles, according to the procedure detailed at the first visit (7). Briefly, they were instructed to use their bilateral hypothenars to massage the symptomatic temporal and/or masseter muscles at the tender point for 30 s each.…”
Section: Tpi and Sm Treatmentmentioning
confidence: 99%
“…MPS is easily misdiagnosed, which can lead to mistreatment (1)(2)(3)(4). Although various methods have been used to assess masticatory MPS and its treatment-such as visual analog scale (VAS) score, pressure pain threshold, maximum mouth opening, tooth contact ratio, magnetic resonance elastography, ultrasound imaging, and Doppler flow waveform-evaluation is not standardized and remains controversial (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%